Burnout levels of assistant physicians working at a Turkish university hospital - Pirincci, Edibe; Vicdanli, Safiye Selcen (SEAMEO TROPMED Network, 2015)
The purpose of the present study was to determine their current levels of burnout and to identify the factors associated with burnout syndrome among assistant physicians who are undergoing further training in medical specialties. The present descriptive study was conducted on assistant physicians at a Turkish university hospital. The participants were subject to a 26-item questionnaire and the Maslach Burnout Inventory (MBI). The mean age of the participants was 29.95± 3.79 years. Their mean scores in the three sub-scales of the MBI were as follows: 22.33±8.37 in emotional exhaustion (EE), 8.72±4.74 in depersonalization (D), and 18.76±5.87 in personal accomplishment (PA). While there were no significant discrepancies among the respondents in terms of their mean scores in EE, D and PA depending on their gender, age groups and marital status, those who considered their monthly income levels as “poor” differed significantly from those who regarded their monthly income levels as “good” in terms of their mean scores in EE, D, and PA. In addition, there was a significant difference in terms of the mean scores in EE, D, and PA between the participants who were appreciated by their superiors and those who were not. The participants had high, low and average mean scores in EE, PA and D, respectively, suggesting that they had high levels of burnout in reference to EE and PA and average levels of burnout in reference to D. © 2015, Southeast Asian Journal of Tropical Medicine and Public Health. All rights reserved.
Keywords: Assistant physicians; Burnout syndrome; Maslach burnout inventory; Turkey; University hospital